2020
DOI: 10.1155/2020/7136802
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Atrial Septal Defect Closure Using the Occlutech Figulla Device in Adults: More than 800 Patient-Years of Follow-Up

Abstract: Purpose. The Occlutech Figulla occluder has been proven safe and effective at midterm follow-up after percutaneous atrial septal defect (ASD) closure. We describe the safety and efficacy at long-term follow-up in adults. Methods. All consecutive adult patients that underwent ASD closure between 2008 and 2015 were included. All complications were registered. Residual left-to-right shunt (LRS) was diagnosed using color-Doppler transthoracic echocardiography (TTE). Right-to-left shunting was diagnosed using contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 16 publications
0
16
0
3
Order By: Relevance
“…The screw mechanism of the ASO was replaced by a ball-shaped connector design that allows a tilt angle up to 45° with better septum alignment during implantation. The system was even upgraded in the third-generation device (Flex II) to a bioptome-like innovative delivery system that comes along with a steerable catheter, allowing full circular movement of the device on the delivery wire and facilitating closure of larger or asymmetric defects ( 20 , 21 ). However, this device carries 2 major drawbacks ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The screw mechanism of the ASO was replaced by a ball-shaped connector design that allows a tilt angle up to 45° with better septum alignment during implantation. The system was even upgraded in the third-generation device (Flex II) to a bioptome-like innovative delivery system that comes along with a steerable catheter, allowing full circular movement of the device on the delivery wire and facilitating closure of larger or asymmetric defects ( 20 , 21 ). However, this device carries 2 major drawbacks ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The Cardioseal/Starflex device is no longer available for ASD closure due to a high complication rate (device embolization and device fracture). Though, Butera et al found a non-significant difference in embolization rate between the Cardioseal/Starflex device and the Amplatzer device (respectively 2.5% and 0.7%), our embolization rate was 10.7% using the Cardioseal/Starflex device [77,[80][81][82][83]. One of the difference between both studies is the lager diameter of the ASD closed and used device, which is known to be associated with embolization.…”
Section: Complicationsmentioning
confidence: 61%
“…There were no AV-blocks in our studies using the Occlutech-, Amplatzer-or Cardioseal/Starflex device [77,82]. There was one patient with device thrombosis in our study using the Occlutech device, however, this patient was noncompliant using coumadin for atrial fibrillation [82]. The etiology of pericardial effusion remains unclear.…”
Section: Complicationsmentioning
confidence: 63%
See 2 more Smart Citations